Analisis Kebutuhan Pelatihan dalam Meningkatkan Kinerja Karyawan: Studi Kasus pada Karyawan Koperasi Produsen Tempe Tahu Indonesia (Kopti) Kota Bandung - Fauziah Andriani; Siti Maryam; Dindin Burhanudin (J-Coop : Journal of Co-operative, 2026)
The issue of employee performance that has not yet reached its full potential at the cooperative indicates a gap between employees’ actual competencies and job requirements. This study aims to describe training needs and employee performance, as well as to formulate performance improvement efforts at the Indonesian Tempe and Tofu Producers Cooperative (Kopti) in Bandung. Theresearch method used was a case study with a descriptive quantitative approach. The research sample was purposively selected to include 7 employees responsible for transaction recording and bookkeeping. Data collection was conducted through questionnaires,observations, interviews, and a literature review. The results indicate that the training needs analysis falls into the “needed” category (score of 77.46%). Although overall operational performance was assessed as fairly good, major challenges were identified in the areas of efficient use of work time and understanding of digital technology. This study recommends the implementation of computerization and administrative digitization training as strategic steps for the cooperative.